PRAME peptide‐specific CD8+ T cells represent the predominant response against leukemia‐associated antigens in healthy individuals. Issue 8 (8th July 2018) - Matko, Sarah; Manderla, Julia; Bonsack, Maria; Schmitz, Marc; Bornhauser, Martin; Tonn, Torsten; Odendahl, Marcus
Abstract: Antigen‐specific T cells isolated from healthy individuals (HIs) have shown great therapeutic potential upon adoptive transfer for the treatment of viremia in immunosuppressed patients. The lack of comprehensive data on the prevalence and characteristics of leukemia‐associated antigen (LAA)‐specific T cells in HIs still limits such an approach for tumor therapy. Therefore, we have investigated T‐cell responses against prominent candidates comprising Wilms' tumor protein 1 (WT1), preferentially expressed antigen in melanoma (PRAME), Survivin, NY‐ESO, and p53 by screening PBMCs from HIs using intracellular IFN‐γ staining following provocation with LAA peptide mixes. Here, we found predominantly poly‐functional effector/effector memory CCR7 − /CD45RA +/− /CD8 + LAA peptide‐specific T cells with varying CD95 expression in 34 of 100 tested HIs, whereas CD4 + T cells responses were restricted to 5. Most frequent LAA peptide‐specific T cell responses were directed against WT1 and PRAME peptides with a prevalence of 20 and 17%, respectively, showing the highest magnitude (0.16% ± 0.22% (mean ± SD)) for PRAME peptides. Cytotoxicity of PRAME peptide‐specific T cells was demonstrated by specific killing of PRAME peptide‐pulsed T2 cells. Furthermore, the proliferative capacity of PRAME peptide‐specific T cells was confined to HIs responsive toward PRAME peptide challenge corroborating the accuracy of the screening results. In conclusion, we identified PRAME as a promising target antigen for adoptive leukemia therapy. Abstract : Screening PBMCs of healthy individuals (HI) with LAAs peptide mixes in the search for therapeutic antigen‐specific T cells PRAME peptide‐specific CD8 + T cells were identified as the predominant T‐cell response against tested LAAs. Proliferative capacity of PRAME peptide‐specific CD8 + T cells were confined to HI responsive toward PRAME peptide challenge corroborating the accuracy of the screening and suggesting PRAME as a promising target antigen for adoptive immunotherapy.